Functional characterisation of synuclein-based novel genetic mouse models - Anwar, S (2011)
Synucleins are highly conserved presynaptic proteins with unknown function. α-synuclein plays a key role regulating dopamine homeostasis and is intimately involved in Parkinson’s disease (PD) pathogenesis. However, the normal/pathological role of α-synuclein remains unidentified. Studies exploring its function are limited as current transgenic mouse models do not fully recapitulate PD pathology. This thesis reports the functional characterisation of two novel synuclein-based mouse models. I report the molecular and functional characterisation of transgenic mouse lines with wild-type or A30P-mutant human α-synuclein genomic locus carried within a bacterial artificial chromosome. SNCA-A30P+Snca-/- mice exhibited a highly physiologically relevant expression pattern of the transgene, including expression in the substantia nigra pars compacta (SNpc) and a specific, age-related loss of TH+ cells in the SNpc, the key region of preferential cell loss in PD, compared with non-transgenic Snca -/- littermate controls. Analysis of dopamine signalling using fast-scan cyclic voltammetry (FCV) showed young adult SNCA-A30P+Snca-/- mice had an approximately 20% lower evoked extracellular dopamine concentration ([DA]o) compared with non-transgenic Snca -/- littermate controls, a decrease specific to the dorsal striatum. This difference diminished with age and could not be attributed to changes in dopamine reuptake/content. I detail the behavioural and neurochemical phenotype in mice lacking all three synucleins (α/β/γ). Functional compensation between synucleins emphasises the importance of studying their effects by removing all three proteins simultaneously. Triple-null mice exhibited hyperactivity in a novel environment reminiscent of a hyperdopaminergic-like phenotype, but showed no phenotype in anxiety or motor related tests. FCV revealed synuclein triple-null mice had a two-fold increase in [DA]o, specific to the dorsal striatum and not attributable to changes in dopamine reuptake/content, changes in striatal nicotinic receptor activity nor calcium-dependent changes in dopamine exocytosis. Together, the analysis from these two novel mouse models reveal synucleins play an important role in altering synaptic function in the dorsal striatum (the region selectively affected in PD) and contributes to growing evidence suggesting synucleins are negative regulators of synaptic dopamine release.